2016
DOI: 10.3906/biy-1501-61
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of chondrogenic differentiation potential of equine adiposetissue-derived mesenchymal stem cells using TGF-β3 and BMP-6

Abstract: This study was designed to evaluate the in vitro chondrogenic differentiation potential of equine adipose tissue-derived mesenchymal stem cells (AT-MSCs) in response to different culture conditions. Fat tissue cells after collection were cultured in optimized conditions until passage 3 (P3). P3 cells were cultured as micropellets under different chondrogenic conditions for 21 days in 5 groups: basic medium as a control, basic chondrogenic medium (BCM), BCM supplemented with transforming growth factor beta 3 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
1
1
Order By: Relevance
“…In addition, we did not observe the lacuna formation typical for hyaline cartilage. This finding was in contrast to the results documented by Shademan et al (2015), who recorded lacunae in their pellets. They used pellet culture system with more complex chondrogenic medium consisted of dexamethasone, ascorbic acid, ITS, TGF-β3 and BMP-6.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, we did not observe the lacuna formation typical for hyaline cartilage. This finding was in contrast to the results documented by Shademan et al (2015), who recorded lacunae in their pellets. They used pellet culture system with more complex chondrogenic medium consisted of dexamethasone, ascorbic acid, ITS, TGF-β3 and BMP-6.…”
Section: Discussioncontrasting
confidence: 99%
“…It provides 3D architecture of tissue in which the cells are in deep contact and may influence each other by paracrine signaling (Mara et al 2010). This effect is also additively enhanced by supplementation of growth factors such as TGF-β1, TGF-β3, BMP-2, BMP-6 and GDF-5 (Murphy et al 2015;Shademan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrogenic differentiation of MSCs has been described using different induction mediums containing e.g. transforming growth factor β 3 (TGF-β 3 ) and BMP6 [ 56 , 57 ]. Selection of chondrogenic induction medium containing TGF-β 1 and dexamethasone for the present study was based on large, high-throughput mRNA profiling studies, showing this cocktail enhanced expression of hyaline articular cartilage markers, while downregulating unwanted pro-osteogenic markers [ 19 , 58 ].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In the triangle of tissue engineering, in addition to having a suitable cell source and an ideal scaffold, culture medium has an important consequence on tissue regeneration, especially in inducing cellular differentiation (Sheykhhasan, Qomi, Kalhor, Mehdizadeh, & Ghiasi, ). Previous studies in cartilage regeneration have shown that chondro‐inductive factors such as fibroblast growth factor‐2 (Hildner et al, ; Ito, Sawada, Fujiwara, & Tsuchiya, ), insulin‐like growth factor‐1 (Jaklenec et al, ), platelet‐derived growth factor (PDGF; Kang et al, ; Ng et al, ), bone morphogenetic protein‐6 (BMP‐6; Cheng, Gustafson, Tooley, & Zhang, ; Shademan, Parham, & Dehghani, ), and transforming growth factor beta‐3 (TGF‐β3; Almeida et al, ; Shademan et al, ) play an important role in differentiation of MSCs into chondrocytes. Alpha granules present in platelet‐rich plasma (PRP), containing high amounts of TGF‐β3 and other growth factors, are widely used to treat osteoarthritis (Okuda et al, ).…”
Section: Introductionmentioning
confidence: 99%